A Comparison of the J‐1 Visa Waiver and Loan Repayment Programs in the Recruitment and Retention of Physicians in Rural Nebraska. Issue 3 (18th February 2015) - Opoku, Samuel T.; Apenteng, Bettye A.; Lin, Ge; Chen, Li‐Wu; Palm, David; Rauner, Thomas
Abstract Purpose There is a dearth of literature evaluating the effectiveness of programs aimed at recruiting and retaining physicians in rural Nebraska. Taking advantage of the Nebraska Health Professional Tracking System, this study attempts to comparatively assess the effectiveness of the J‐1 visa waiver and state loan repayment programs in the recruitment and retention of physicians in rural Nebraska. Methods A mixed methods approach was used. We tracked 240 physicians who enrolled in the J‐1 visa waiver and state loan repayment programs between 1996 and 2012 until 2013. In addition, key informant interviews were conducted to obtain perspectives on the recruitment and retention of physicians in rural Nebraska through the 2 programs. Findings Results from multilevel survival regression analysis indicated that physicians enrolled in the J‐1 visa waiver program were more likely to leave rural Nebraska when compared with those enrolled in the state loan repayment program. Participants in the qualitative study, however, cautioned against declaring one program as superior over the other, given that the 2 programs addressed different needs for different communities. In addition, results suggested that fostering the integration of physicians and their families into rural communities might be a way of enhancing retention, regardless of program. Conclusion The findings from this study highlight the complexity of recruitment and retention issues in rural Nebraska and suggest the need for more holistic and family‐centered approaches to addressing these issues.